(untitled) (Journal of Humanitarian and Applied Sciences, 2025)
This research examines the problematic nature of recording the events of the Great Fitna in Islamic heritage, focusing on the historians who documented it rather than retelling the events themselves. It argues that the history of the Fitna did not reach us as a direct contemporary record, but as a complex historical construct compiled centuries later within shifting political and sectarian contexts. The study reviews major historiographical schools, including early narrators such as Abu Mikhnaf and Sayf ibn ʿUmar, as well as later compilers like al-Tabari and al-Baladhuri, highlighting how their backgrounds and biases shaped the transmitted material. It also analyzes the fundamental divide between two major narrative trends: the conspiracy narrative, which attributes the Fitna to an external instigator (ʿAbdullah ibn Sabaʾ), and the internal conflict narrative, which emphasizes economic and social factors as the true causes. Finally, the research explores how leading historiansal-Tabari, al-Baladhuri, and Ibn Kathir addressed these conflicting accounts.